Citizen science : guide for families : taking part in real science - Landgraf, Greg (Huron Street Press, 2013)
"People of all ages and backgrounds can discover how to contribute to real scientific research with this handy guide. It defines citizen science, providing an overview of the social and community aspects behind the idea. The book is organized by topic and features links to library resources and descriptions of books appropriate to the subject. In addition, a section devoted to ongoing citizen-science programs includes detailed descriptions for parents and children to identify projects appropriate to their interests, abilities, commitment levels, and locations. Accessible for the whole family, this invaluable resource provides the tools for building strong families as well as improving the global community"--Resumé vydavatele